2021
DOI: 10.3390/nu13082761
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Concentrations and Atopic Dermatitis in Early Childhood: Findings from the Japan Environment and Children’s Study

Abstract: Vitamin D (VitD) may affect immune system modulation and result in the development of atopic dermatitis (AD). However, published findings have remained controversial. We investigated the association between early-life 25-hydroxyvitamin D (25(OH)D) levels and AD risk at childhood with a birth cohort. The data were obtained from “the Japan Environment and Children’s Study (JECS)” and “the Sub-Cohort study of JECS” performed with children aged 2 years. “Liquid chromatography-tandem mass spectrometry” was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Although serum 25(OH)D concentration is the best marker to reflect VD concentrations in the body, no single cutoff value has been agreed upon by health agencies for serum 25(OH)D concentration to define VDD. Second, serum VD status was evaluated according to a single blood test, which may not reflect long-term VD in the body very well [ 20 , 21 ]. Third, a value of 25(OH)D was truncated as 4 in this study if a value of serum 25(OH)D2 or 25(OH)D3 was lower than 4 ng/mL, which may cause an overestimation of VD level [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although serum 25(OH)D concentration is the best marker to reflect VD concentrations in the body, no single cutoff value has been agreed upon by health agencies for serum 25(OH)D concentration to define VDD. Second, serum VD status was evaluated according to a single blood test, which may not reflect long-term VD in the body very well [ 20 , 21 ]. Third, a value of 25(OH)D was truncated as 4 in this study if a value of serum 25(OH)D2 or 25(OH)D3 was lower than 4 ng/mL, which may cause an overestimation of VD level [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, serum VD status was evaluated according to a single blood test, which may not reflect long-term VD in the body very well [ 20 , 21 ]. Third, a value of 25(OH)D was truncated as 4 in this study if a value of serum 25(OH)D2 or 25(OH)D3 was lower than 4 ng/mL, which may cause an overestimation of VD level [ 18 , 20 ]. Fourth, the information on tobacco smoke exposure was collected from the questionnaires, which may underreport smoking and could not reflect the precise degree of exposure to tobacco overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lucas et al suggested no statistically significant difference of blood 25(OH)D 3 levels between atopic dermatitis patients and controls [13]. A cohort study of 4378 children indicated that low 25(OH)D levels at the age of two years old was not a risk factor for the development of atopic dermatitis at age of three years of age [14]. Most of the published studies have focused on the associations between the serum concentrations of 25(OH)D or 25(OH)D 3 and diseases, but the role of C3-epi-25(OH)D 3 in psoriasis, atopic dermatitis, and vitiligo has not been studied yet.…”
Section: Introductionmentioning
confidence: 98%
“…These findings suggest that vitamin D might play a role in calcium homeostasis, immune regulation, anti-bacterial, and anti-inflammation. Early epidemiological studies have reported associations of blood 25(OH)D or 25(OH)D 3 levels with psoriasis, atopic dermatitis, and vitiligo [10][11][12], but concluded conflicting association results [13][14][15][16]. For example, Ng et al found a significantly lower blood 25(OH)D level in atopic dermatitis patients than healthy controls and low serum vitamin D levels were associated with disease severity [10].…”
Section: Introductionmentioning
confidence: 99%